Targeting metabolism of breast cancer and its implications in T cell immunotherapy - Zou, Jialuo; Mai, Cunjun; Lin, Zhiqin; Zhou, Jian; Lai, Guie (Frontiers in Immunology, 2024)
Breast cancer is a prominent health issue amongst women around the world. Immunotherapies including tumor targeted antibodies, adoptive T cell therapy, vaccines, and immune checkpoint blockers have rejuvenated the clinical management of breast cancer, but the prognosis of patients remains dismal. Metabolic reprogramming and immune escape are two important mechanisms supporting the progression of breast cancer. The deprivation uptake of nutrients (such as glucose, amino acid, and lipid) by breast cancer cells has a significant impact on tumor growth and microenvironment remodeling. In recent years, in-depth researches on the mechanism of metabolic reprogramming and immune escape have been extensively conducted, and targeting metabolic reprogramming has been proposed as a new therapeutic strategy for breast cancer. This article reviews the abnormal metabolism of breast cancer cells and its impact on the anti-tumor activity of T cells, and further explores the possibility of targeting metabolism as a therapeutic strategy for breast cancer.